Assessment of the incidence of venous thromboembolism in patients with Covid-19 admitted to an intensive care unit - Simone V. GROLL; Alessandra SANTOS; Luciane F. CALDEIRA; Andreia C. SANCHES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: To assess the incidence of venous thromboembolism (VTE) in patients hospitalized in an intensive care unit (ICU) due to Covid-19, its relationship with D-dimer levels and other possible associated factors. Method: A cross-sectional and retrospective study, carried out in a public university hospital, between April and June 2021. The sample consisted of patients ≥ 15 years old with positive reverse transcription polymerase chain reaction (RT-PCR) for Sars-CoV-2, excluding pregnant and postpartum women who had ICU admission. Data were collected and tabulated in the Microsoft Office Excel ® program and analyzed using the R Studio® software. Continuous variables were expressed as mean and standard deviation, and categorical variables were expressed as absolute (n) and relative (%) frequencies, and analyzed by Chi-square, a confidence level <0.05 was adopted. Results: The study consisted of 144 patients (61.1% male), with a mean length of stay in the ICU of 14.2±10.3 days. The incidence of deep vein thrombosis (DVT) in these patients was 19% and 5% for pulmonary thromboembolism (PTE). Regarding the D-dimer test, it was noted that the group with the presence of DVT+PTE had a higher median. In total, 31.2% patients were anticoagulated. There was a statistically significant relationship between the performance of hemodialysis and the clinical outcome of death (p<0.05). Conclusion: It is concluded that 21% of the evaluated patients had VTE during their stay in the ICU. The study contributed to characterizing the profile of patients with Covid-19 admitted to the ICU who developed VTE, with the purpose of presenting consistent data that will allow improving the planning of the health care process.